True home improvement - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Beating Hunger: The Chivi experience. A community-based approach to food security in Zimbabwe. By K Murwira, H Wedgewood, C Watson & E J Win, Intermediate Technology Publications, 2000. 150 pp. ISBN 1 85339 524 2 GBP 12.95 Euro 20.95